2021
DOI: 10.1186/s43141-021-00220-4
|View full text |Cite
|
Sign up to set email alerts
|

An immunoinformatics study: designing multivalent T-cell epitope vaccine against canine circovirus

Abstract: Background Canine circovirus is a deadly pathogen of dogs and causes vasculitis and hemorrhagic enteritis. It causes lethal gastroenteritis in pigs, fox, and dogs. Canine circovirus genome contains two main (and opposite) transcription units which encode two open reading frames (ORFs), a replicase-associated protein (Rep) and the capsid (Cap) protein. The replicase protein and capsid protein consist of 303 amino acids and 270 amino acids respectively. Several immuno-informatics methods such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…The major requirement of codon biasness study assists in determining amino acids expressed patterns that can be linked to epitope-based vaccine predictions. In recent studies, for SARS-CoV2 [ 30 , 31 ], dengue [ 32 , 33 ], Nipah [ 34 ], Candida fungus [ 35 ], Canine circovirus [ 36 ], and Zika virus [ 37 ], vaccine predictions were found to be successful. So, codon usage pattern determination can be considered as the preliminary step before deploying any ANN (artificial neural networking)-based web server/tool like NetMHC server for screening essential epitopes of small peptidal length (8–12 amino acids).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major requirement of codon biasness study assists in determining amino acids expressed patterns that can be linked to epitope-based vaccine predictions. In recent studies, for SARS-CoV2 [ 30 , 31 ], dengue [ 32 , 33 ], Nipah [ 34 ], Candida fungus [ 35 ], Canine circovirus [ 36 ], and Zika virus [ 37 ], vaccine predictions were found to be successful. So, codon usage pattern determination can be considered as the preliminary step before deploying any ANN (artificial neural networking)-based web server/tool like NetMHC server for screening essential epitopes of small peptidal length (8–12 amino acids).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, drug repurposing was made easy against harmful pathogens by deploying bioinformatic approaches [ 39 ]. Similarly, for animal models, viral pathogenic proteomes were screened for vaccine designing by deploying immunoinformatics [ 33 , 36 , 40 ]. This study is unique in terms of saving time and money for peptide-based vaccine crafting.…”
Section: Discussionmentioning
confidence: 99%
“…(De Groot et al 2002 ; Sharma et al 2018 ). In current scenario, the advent of immunoinformatics tools and databases are helping in the development of multi epitope vaccines, which rising as a new hope to resolve all above limitations of conventional vaccines for human pathogenic viruses, bacteria (Joshi and Kaushik 2020 ), fungi (Akhtar et al 2021 ) as well as veterinary pathogens also (Jain et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…( Kumar et al 2013 ; Sharma et al 2014 , 2021 ). Recently, other than these human pathogens zika virus, fungal pathogen as well as veterinary pathogens also showed potential results in development of epitope vaccine (Sharma et al 2019 ; Jain et al 2021 ). In several studies, epitope based vaccine immunizations against various infections showed significant results with proven cellular as well as humoral immunity (Hajissa et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, epitope-based vaccine candidates were successfully developed against SARS-CoV-2, human cytomegalovirus, Tropheryma whipplei , nervous necrosis virus, candida fungus, and dengue virus (Akhtar et al 2021a , b , c ; Sunil Krishnan et al 2020 ; Jain et al 2021 ; Joshi et al 2020 ; Joshi and Kaushik 2020 ; Krishnan et al 2021 ). Subunit vaccines have been clinically approved for use against pertussis, influenza, Streptococcus pneumoniae , and Haemophilus influenzae type b (Folegatti et al 2020 ; Koch et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%